ANALISIS CRYPTOCURRENCY SEBAGAI ALAT ALTERNATIF DALAM BERINVESTASI DI INDONESIA PADA MATA UANG DIGITAL BITCOIN - Muhammad Naufal Hasani; Sardjono; Ramadhan, Muhammad; Mariyani, Kristin; Setiawan, Reksa; Sucidha, Irma (Jurnal Ilmu Ekonomi dan Bisnis, 2022)
The purpose of this research is to find out cryptocurrency investment as an alternative investment tool in Indonesia, especially in bitcoin digital currency and how the legal regulations regulate it. The type of research in this study is qualitative, where researchers get an overview of cryptocurrency investment. The data analysis technique used is literature study, observation and interviews. This research was conducted for more than 3 months. The results of the study show that the legal position of using cryptocurrency as an investment tool is not prohibited. This is found in the provisions of Bappebti which regulates whether or not the investment may be enforced, as long as it does not conflict with state regulations, in essence it can be used. Cryptocurrency investment in Indonesia is also increasing very rapidly because the price of Bitcoin continues to increase, causing more and more people to compete to invest in this bitcoin digital asset. Keywords: Cryptocurrency, Investment, Bitcoin